Islamic values in a multi-cultural society - Babu Sahib, Hikmatullah; Demirel, Serdar (Sakarya University, 2010)
Muslims have never lived in total isolation. With the disintegration of the Muslim Caliphate and the subsequent diasporas from their heartlands to much ‘greener pastures’ in pursuit of betterment or in compliance with the Prophetic directive of conveying the message of IslÉm, Muslims the world over have come in contact, more so, increasingly, with other dominant cultures. This phenomena, however, is not something new to IslÉm. In fact a study of its origin sheds adequate light on the early blossoming of IslÉm under a multi-cultural environment. What really concerns the Muslims today is not the relevance or otherwise of the IslÉmic values to them, but rather how best Minority-Muslims could accommodate the presence of other values of other dominant cultures, with whom they have to sometime share a common political destiny. Can these accommodated values constitute IslÉmic values? Are IslÉmic values the exclusive rights of Muslims or can they be shared with others as universal values? Is there a need to have separate universal values? If there is, can those existing universal values be considered as IslÉmic values? What is the notion of good and bad in IslÉm? Can the good values of all cultures be considered as IslÉmic? How such cross-cultural fertilization of values can and has benefited Muslims and others in a multi-cultural society? And what new value, if any, IslÉm gains from such cross-cultural encounters? These are some of the issues this paper attempts to address. The writers feel that IslÉmic values, though rooted in the Qur’Én and sunnah, continue to evolve to spatio-temporal needs. They believe that encounters of disparate values are essential for the continued relevance of the IslÉmization of values by presenting the invaluable opportunities for critically examining the values of the dominant cultures and reassessing Muslim cultural-values in the light of Qur’Én and sunnah.